Implementasi Model Pembelajaran Berbasis Project Based Learning untuk Meningkatkan Pemahaman Mahasiswa terhadap Praktik Organizing Event - Trisnayoni, Raden Ayu; Ayu Puspita, Ni Putu Lianda; Dewi, Ni Wayan Sintya (Jurnal Ilmiah Pariwisata; Vol 29 No 2 (2024): Jurnal Ilmiah Pariwisata, 2024)
The aim of this research is to improve students' understanding and practical skills in organizing events. The PBL (Project Based Learning) model is proven to help students develop critical thinking, problem solving, collaboration and communication skills. The method in this research is direct observation of the research subjects, namely class V A MBP students who received the event organizing course, unstructured interviews with students and all parties involved in class V A student projects, and literature methods by collecting references from previous research discussing PBL . The research results show that this PBL model approach is effective in increasing students' understanding, critical skills, collaboration and creativity. The practice of event organizing projects is also relevant to the world of the events industry, strengthening students' motivation and preparing them for future challenges. Students gain a deep understanding of industry event hosting practices, as evidenced by the success of their projects. Even though PBL has significant advantages and positive benefits, careful planning is needed starting in the fourth semester to reduce risks in the following semester. Keywords: implementation, learning model, project based learning, organizing event